تقييم اجراء القلع السني عند المرضى متلقي مضاد التصاق الصفيحات أحادي و/أو ثنائي الدواء - خليل عبد الكريم; حمدان أحمد (Latakia University Journal -Medical Sciences Series, 2018)
Objectives: The aim of this study is to evaluate the possibility of dental extraction in patients receiving Antiplatelet drugs, and to achieve this extraction safely, without any danger to the patient in terms of bleeding after surgery. Materials and Methods: In 20 patients receiving Antiplatelet drugs, 10 were receiving aspirin alone and 10 received aspirin with Clopidogrel. Simple extractions were performed in these patients, bleeding was monitored and bleeding time was assessed in both groups. Results: It was observed that the bleeding time in both groups was longer and the time was a little greater in the second group receiving aspirin with Clopidogrel. Conclusion: Based on this study, we found that taking aspirin alone can be done without the need to stop the medication. In the case of aspirin with clopidogrel, it is preferable to evaluate the time of bleeding, especially if the extraction is multiple. الأهداف: تهدف هذه الدراسة الى تقييم إمكانية القلع السني عند المرضى متلقي مضاد التصاق الصفيحات وإنجاز ذلك القلع بشكل امن لايشكل أية خطورة على المريض لجهة النزف مابعد العمل الجراحي. المواد والطرائق: تم إجراء القلع لدى 20 مريضا من متلقي مضاد التصاق الصفيحات 10 منهم يتلقون الأسبرين لوحده و10 منهم يتلقى الأسبرين مع الكلوبيدوغريل. تم اجراء قلوع بسيطة عند هؤلاء المرضى ومراقبة النزف وتقييم زمن النزف لدى كل من المجموعتين. النتائج: تم ملاحظة أن زمن النزف لدى كل من المجموعتين كان متطاولاً ولكن التطاول كان أكبر لدى المجموعة الثانية الذين يتلقون الأسبرين مع الكلوبيدوغريل. الاستنتاجات: استناداً الى هذه الدراسة وجدنا أنه يمكن إجراء القلع لدى المريض الذي يتناول الأسبرين لوحده دون الحاجة إلى إيقاف الدواء بينما في حالة تناول الأسبرين مع الكلوبيدوغريل يفضل تقييم زمن النزف خاصة اذا كان القلع متعدد.